2021
DOI: 10.1186/s12870-021-03290-1
|View full text |Cite
|
Sign up to set email alerts
|

Deep transcriptomic study reveals the role of cell wall biosynthesis and organization networks in the developing shell of peanut pod

Abstract: Background Peanut (Arachis hypogaea L.) belongs to an exceptional group of legume plants, wherein the flowers are produced aerially, but the pods develop under the ground. In such a unique environment, the pod’s outer shell plays a vital role as a barrier against mechanical damage and soilborne pathogens. Recent studies have reported the uniqueness and importance of gene expression patterns that accompany peanut pods’ biogenesis. These studies focused on biogenesis and pod development during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 101 publications
(98 reference statements)
0
4
1
Order By: Relevance
“…Our results contrast with other recent research, which identified shattering QTL located on chromosomes Pv03, Pv05, Pv08, and Pv09 (Rau et al, 2019;Parker et al, 2020). Legume pod dehiscence is known to be controlled by downstream NAC and MYB family transcription factors which also regulate the formation of secondary cell walls (Nakano et al, 2015;Ohtani and Demura, 2019;Takahashi et al, 2020;Watcharatpong et al, 2020;Zhang and Singh 2020;Chen et al, 2021;Gupta et al, 2021). Additional genes responsible for controlling legume shattering, such as the soybean dirigent gene PDH1 and PvPdh1 in common bean, influence the torsion of pod valves without causing anatomical alterations, as observed in studies by Suzuki et al (2009) and Parker et al (2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results contrast with other recent research, which identified shattering QTL located on chromosomes Pv03, Pv05, Pv08, and Pv09 (Rau et al, 2019;Parker et al, 2020). Legume pod dehiscence is known to be controlled by downstream NAC and MYB family transcription factors which also regulate the formation of secondary cell walls (Nakano et al, 2015;Ohtani and Demura, 2019;Takahashi et al, 2020;Watcharatpong et al, 2020;Zhang and Singh 2020;Chen et al, 2021;Gupta et al, 2021). Additional genes responsible for controlling legume shattering, such as the soybean dirigent gene PDH1 and PvPdh1 in common bean, influence the torsion of pod valves without causing anatomical alterations, as observed in studies by Suzuki et al (2009) and Parker et al (2020).…”
Section: Discussioncontrasting
confidence: 99%
“…37 In this study, 92.31% high-abundance DEGs of the ethylene signal pathway exhibited completely opposite expression trends in comparisons T1-v-T2 and T2-v-T3. Moreover, Gupta et al 41 found that there exists a strong interaction between ethylene and auxin during pod development, and this interaction is critical for peanut pod development. According to our results, we found that microplastics contamination in the geocarposphere soil caused serious interference with the expressions of auxin and ethylene signaling pathway genes in peanut pod, which affected the synergistic regulation of pod development by auxin and ethylene, whereas the application of biochar could correct these disruptions caused by microplastics contamination, and effectively restore the development of peanut pod in a microplasticscontaminated geocarposphere soil.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 92.31% high‐abundance DEGs of the ethylene signal pathway exhibited completely opposite expression trends in comparisons T1‐v‐T2 and T2‐v‐T3. Moreover, Gupta et al 41 . found that there exists a strong interaction between ethylene and auxin during pod development, and this interaction is critical for peanut pod development.…”
Section: Discussionmentioning
confidence: 99%
“…In the current work, RNA-seq analysis indicated bidirectional changes in the expression of cell wall-related genes, which may be involved in both the continuing abscission process and the growth of undescended organs ( Merelo et al., 2017 ; Wu et al., 2021 ). Pathways associated with cell wall formation, including cell wall biogenesis, galactose and mannose metabolism, aminoglycan, pectin synthesis, and other related genes, exhibited divergent patterns at various phases of CHF and CF ( Wilmowicz et al., 2021 ; Gupta et al., 2021 ). Cell wall production is accompanied by active cell division; several cell wall-related genes may play highly specialized roles in cell wall modification, and some of these gene products may be essential for the optimal function of other genes.…”
Section: Discussionmentioning
confidence: 99%